(untitled) (Journal of Organizational Psychology, 2022)
With stress documented beyond inherent levels in our initial research with Canadian teachers during the COVID-19 pandemic, this case study moves beyond the consideration of individual strategies to reduce burnout, toward an examination of situational approaches to support teachers during this time of disruptive change. Using the Areas of Worklife Model, we present an analysis of in-depth interviews and focus groups with Canadian educational leaders on key transformational leadership approaches that were applied during the COVID-19 pandemic. In addition to observations about contextual factors which led to imbalance and adversity for teachers, insights were gained into leadership approaches which conversely increased balance and engagement resulting in overall enhanced teacher resilience.